The importance of inspecting the inoculum's methane production for estimating kinetic parameters in biochemical methane potential tests. (June 2023) - Steindl, Matthias; Dandikas, Vasilis; Lichti, Fabian; Höcherl, Susanne; Koch, Konrad
Graphical abstract: Highlights: First-order kinetic model applied to SMP curves from 3 inocula and 2 substrates. First-order kinetic constant k differed between inocula for the same substrate. BMP validation criteria were not able to identify an unsuitable inoculum. SMP curves of blanks were used to identify a suitable inoculum for kinetic analysis. Validation criteria for estimating first-order kinetic constant k are proposed. Abstract: The aim of this study was to improve the quality of estimations of the first-order kinetic constant k, in Biochemical Methane Potential (BMP) tests. The results showed that existing guidelines for BMP tests are not sufficient to improve the estimation of k . The methane production of the inoculum itself exerted a major influence on the estimation of k . A flawed value in k was correlated with a high endogenous methane production. Excluding blanks that showed a distinct lag-phase of >1 day and a mean relative standard deviation >10% during the first ten days of a BMP test helped to retrieve more consistent estimates for k . For improving the repeatability in the determination of k in BMP tests, it is strongly recommended to inspect the methane production rate of the blanks. The proposed threshold values may be applied by other researchers but need further verification with different data.